2017
DOI: 10.15516/cje.v19i3.2356
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective on Educational Policies and Their Implementation in the Vocational Teacher Education Provision / Osvrt na obrazovne politike i njihovu provedbu u obrazovanju strukovnih nastavnika

Abstract: Long-standing gaps of teachers' academic qualifications persist despite changes and developments of educational policies the government has continually been making. The gaps eventually result in a gradual decrease in the quality of vocational school graduates, which has recently caused grave national concern. The decrease is evident in Indonesian vocational students' lack of competitive spirit and skills in the national labor market. In an attempt to find a creative and effective solution to this problem, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Applied here were: resources as the independent variable, engagement as the mediating variable, and student learning outcomes as the dependent variable. Although many studies have shown a statistically relevant and positive correlation between demographic factors such as residence status (Astin, 1999;Pascarella, Bohr, Nora, Zusman, Inman, & Desler, 1994), gender, and teacher qualification (Adeyemi & Adeyemi, 2014;Nurhadi, Zahro, & Lyau, 2017) on the one hand, and academic achievement on the other, the present study found out that gender, residence status, faculty qualification, and students' area of specialization did not lead to significant differences between the groups, and therefore, these factors were not considered determinant.…”
Section: Discussionmentioning
confidence: 99%
“…Applied here were: resources as the independent variable, engagement as the mediating variable, and student learning outcomes as the dependent variable. Although many studies have shown a statistically relevant and positive correlation between demographic factors such as residence status (Astin, 1999;Pascarella, Bohr, Nora, Zusman, Inman, & Desler, 1994), gender, and teacher qualification (Adeyemi & Adeyemi, 2014;Nurhadi, Zahro, & Lyau, 2017) on the one hand, and academic achievement on the other, the present study found out that gender, residence status, faculty qualification, and students' area of specialization did not lead to significant differences between the groups, and therefore, these factors were not considered determinant.…”
Section: Discussionmentioning
confidence: 99%
“…The latter implies the introduction of licensing scheme for vocational teachers based on lifelong education programs provided by national centers of competencies in tourism. As argued by Nurhadi et al (2017), the policy on the quality of the future vocational teachers needs to be focused on the development of the certification process and on the establishment of competency standards of licensed vocational teachers;…”
Section: Policy Recommendationsmentioning
confidence: 99%